2021
DOI: 10.1038/s41398-021-01337-3
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid signaling in the lateral habenula regulates pain and alcohol consumption

Abstract: Hyperalgesia, which often occurs in people suffering from alcohol use disorder, may drive excessive drinking and relapse. Emerging evidence suggests that the lateral habenula (LHb) may play a significant role in this condition. Previous research suggests that endocannabinoid signaling (eCBs) is involved in drug addiction and pain, and that the LHb contains core components of the eCBs machinery. We report here our findings in rats subjected to chronic ethanol vapor exposure. We detected a substantial increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 81 publications
8
25
0
Order By: Relevance
“…Similarly, a recent study demonstrated that exposure to alcohol in rats decreases CB1R expression, but in contrast, increases MAGL with no change in FAAH. Interestingly, this study also found that activation of eCB signaling within the LHb is an analgesic and could reduce ethanol intake (Fu et al, 2021). Additionally, KO of MAGL can promote anxiety-and pro-depressive behaviors (Imperatore et al, 2015) providing additional evidence for a critical role of eCB modulation of neural circuits that regulate stress-related behaviors.…”
Section: Els Potentially Impairs Ecb Signaling In the Lhbmentioning
confidence: 52%
“…Similarly, a recent study demonstrated that exposure to alcohol in rats decreases CB1R expression, but in contrast, increases MAGL with no change in FAAH. Interestingly, this study also found that activation of eCB signaling within the LHb is an analgesic and could reduce ethanol intake (Fu et al, 2021). Additionally, KO of MAGL can promote anxiety-and pro-depressive behaviors (Imperatore et al, 2015) providing additional evidence for a critical role of eCB modulation of neural circuits that regulate stress-related behaviors.…”
Section: Els Potentially Impairs Ecb Signaling In the Lhbmentioning
confidence: 52%
“… 147 Consistent with these findings, 12 weeks of CIE vapor reduced Cnr1 and CB 1 levels in the rat lateral habenula, while enhancing levels of the eCB-related mRNA and/or proteins, DAGL-beta, NAPE-PLD mRNA ( napepld ), and MAGL. 152 In contrast, no change in CB 1 receptor binding and mRNA levels occurred in the hippocampus, cerebral cortex, or motor and limbic structures in a chronic ethanol intake model (7% liquid diet for 15 days). 153 …”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, other authors showed that chronic ethanol vapor exposure increases MGLL and DAGLB mRNA and MAGL protein levels. These changes were accompanied by a significant decrease in CNR1 mRNA and CB1R protein levels in alcohol-exposed rats [51]. The implication of CNR1 genes in alcohol intake was also evaluated in a study using the CRISP/CAS9 method.…”
Section: Gene and Protein Function/expression Changes Of Ecs Componentsmentioning
confidence: 99%